Retention and availability of phosphorus associated with organic matter in a typic melanudands of cauca department, colombia (2013)
The effect of organic matter on retention and Phosphorus (P) availability in a Typic Melanudands cultivated coffee (Coffea arabica) and guamo (Inga spuria), was evaluated by isotherms from the Langmuir equation using linearized by Scatchard and using the method proposed by Fox and Kamprath. A completely randomized design with sixty treatments, generated from five concentrations of P for six times of incubation, in soil samples with and without organic matter was used. The analysis of variance no show differences in adsorption of P as a function of time of incubation, indicating that the adsorption occurs from time zero. P retention was adjusted according to the Scatchard isotherm with values L =0.16 x 106(soil with organic matter) and 3 x 106(soil without organic matter), showing that phosphorus adsorption occurs mainly in the mineral fraction. Higher distribution coefficient on soil without organicmatter (9.72) shows many adsorption sites with respect to soil with organic matter (4.08). The upper value of Qmax on soil with organic matter reveals adsorption sites but with low affinity, reflected in lower partition coefficient, showing easy desorption process to the soil solution.